MENCIPTAKAN ITIKAD BAIK YANG BERKEADILAN DALAM KONTRAK ASURANSI JIWA - Zahry Vandawati Chumaida (Yuridika, 2014)
An insured who bind themselves to the insurer to protect his life by taking life insurance, of course, will conduct the closing of the contract of insurance agreements. To close this insurance contract the insured is deemed very essential to peruse the terms and conditions and the rights and obligations that will he get. In many cases it is turned to be extremely detrimental to the insured party when related to the contract of insurance. This is due to a lack of good faith on the part of the insurer to pay insurance claim filed by the insured or beneficiary. Instead, the insured is required to execute an agreement in good faith even at the beginning of the insurance contract the insured has been burdened insurance for acting in good faith.Keywords: contract, good faith, life insurance.